Validity evaluation of the genetics and genomics in nursing practice survey - Plavskin, Alexandra (Nurs Open, 2019)
AIM: To psychometrically test the Genetics and Genomics Nursing Practice Survey (GGNPS) for evidence of content, face and construct validity. DESIGN: This study was a secondary data analysis. METHOD: Data collected from the Method for Introducing a New Competency into Nursing Practice (MINC) study were used to evaluate the GGNPS for evidence of construct validity via structural equation modelling and confirmatory factor analysis. Face validity was evaluated via feedback from practicing RNs without specific experience with or knowledge of genetics/genomics. Content validity was evaluated via content expert feedback and assessment of a content validity index. RESULTS: The thresholds for evidence of content and face validity were met. However, we found less evidence for construct validity of the GGNPS; an exploratory factor analysis, conducted to gain additional insight into the theorized latent constructs, determined that the variables were more interrelated that previously predicted.